The Impact of LED Correlated Color Temperature on Visual Performance Under Mesopic Conditions - Lili Dong; Li Qin; Wenhai Xu; Lidong Zhang (IEEE Photonics Journal, 2017)
The aim of this study was to investigate the impact of correlated color temperature (CCT) of LED light source on human vision performance in mesopic region. First, six CCTs (3500, 4000, 4500, 5000, 5700, and 6500 K) were assessed using mesopic photometry model MES-2. The calculation results indicated that the mesopic luminance had a positive correlation with CCT. Then, reaction time experiment was conducted in an experimental box designed to simulate the mesopic application environments. Ten observers of different ages and gender participated to make response after target appears under different lighting conditions. Experiment results showed that reaction time had a negative correlation with CCT, which is coherent with that the mesopic luminance increased with the increasing of CCT.